AN ANALYSIS OF STUDENTS’ ABILITY IN WRITING DESCRIPTIVE TEXT AT THE ELEVENTH GRADE STUDENT OF SMA NEGERI 5 LUBUKLINGGAU - Elga; ardayati; yulfi (Lingustic, Literature and English Education, 2023)
The problem in this study is "How is the ability of students to write descriptive text?" The purpose of this study was to describe the abilities of students in writing descriptive text. This study uses a quantitative descriptive method for data collected in writing descriptive text. The population in this study is all class XI students of SMAN 5 Lubuklinggau. The sample of this research is XI F4, totalling 35 students who were taken by class using random sampling. Based on the results of writing descriptive text in class XI students of SMAN 5 Lubuklinggau are included in the failed category. The average value of students is 57. There are 4 students (13%) "Very Good", 7 students (24%) are in the "Good" category, 8 students (27%) are included in the "Medium" category, 10 students (34%) are in the "Moderate" category. It means that the student's ability to write descriptive text is included in the failed category. In conclusion, the ability of students to write descriptive texts is still not very good about grammar, vocabulary and grammar.